High‐Yield Electrosynthesis of Formic Acid from CO2 Reduction on Single‐Bismuth Catalyst Loaded on N‐Doped Hollow Carbon Nanospheress - Jihan Zhang; Kun Zhao; Yueming Ma; Weirui Chen; Xinglei Shi; Chenghua Sun; Qianyu Zhang; Junfeng Niu (Small Structures, 2024)
Electroreduction of CO2 into formic acid (HCOOH) is of great economical value and potential for industrialization. However, it is still a substantial challenge due to the lack of efficient catalysts with simultaneously high activity, selectivity, and durability. Herein, a single‐atom bismuth loaded on N‐doped hollow carbon sphere (Bi–SA/NHCS) catalyst is reported and its catalytic activity and selectivity are modulated by changing the coordination structure of Bi center. The obtained Bi–SA/NHCS with a Bi–N3 site exhibits significantly enhanced electrocatalytic activity and selectivity of HCOOH synthesis from CO2 reduction. The HCOOH production rate achieves 16.2 mmol L−1 h−1 cm−2 at a current density of 20 mA cm−2, and its Faradaic efficiency remains 100% during a long‐term reaction. The HCOOH production rate normalized by catalyst loading is at a molar level of nearly 1.5 mol h−1 gcat−1. The production rate and Faradaic efficiency of HCOOH electrosynthesis on Bi–SA/NHCS are significantly boosted as compared with other catalysts reported in the literature. Experimental and density‐functional theory results demonstrate that the boosted activity and selectivity of HCOOH synthesis owe to the electronic structure modulation to the Bi center via threefold coordinated N‐ligands, leading to a proper binding energy of HOCO* intermediates.